Modelling the influence of rainfall, temperature, and humidity on the population dynamics of aedes mosquitoes in Pengkalan Hulu, Perak - Abdul Khalid, Muhammad Kasyfi (2021)
Dengue fever is one of the vector-borne diseases carried by Aedes mosquitoes either Aedes aegypti or Aedes albopictus. This disease is a global issue which is still out of control until today and it is still increasing day by day. The purpose of this study is to identify the factors affecting the density of Aedes mosquitoes in an area in terms of climate change. The three weather factors that been used in this study are rain distribution, ambient temperature, and relative humidity which will be associated with the density of Aedes mosquitoes in Taman Damai and Kampung Baru, Pengkalan Hulu, in the state of Perak. This study uses secondary data obtained from the Malaysian Meteorological Department, which are rainfall distribution, ambient temperature, and humidity data. Besides, ovitrap index data was obtained from the Entomology Unit of Hulu Perak District Health Office. To find the relationship between weather factors and Aedes mosquito densities, the Spearman’s correlation test was used because the data obtained were not normally distributed. The test results found that the density of Aedes mosquitoes in Taman Damai and Kampung Baru Pengkalan Hulu had low correlation with rainfall distribution, moderate correlation with humidity, and no correlation with temperature. The result of this study can be used to determine appropriate methods in reducing the density of Aedes mosquitoes in the study area and in turn can reduce the incidence of dengue fever in the future.